Interbase-FRET binding assay for pre-microRNAs - Mattias Bood (Nature Portfolio, 2021)
Abstract The aberrant expression of microRNAs (miRs) has been linked to several human diseases. A promising approach for targeting these anomalies is the use of small-molecule inhibitors of miR biogenesis. These inhibitors have the potential to (i) dissect miR mechanisms of action, (ii) discover new drug targets, and (iii) function as new therapeutic agents. Here, we designed Förster resonance energy transfer (FRET)-labeled oligoribonucleotides of the precursor of the oncogenic miR-21 (pre-miR-21) and used them together with a set of aminoglycosides to develop an interbase-FRET assay to detect ligand binding to pre-miRs. Our interbase-FRET assay accurately reports structural changes of the RNA oligonucleotide induced by ligand binding. We demonstrate its application in a rapid, qualitative drug candidate screen by assessing the relative binding affinity between 12 aminoglycoside antibiotics and pre-miR-21. Surface plasmon resonance (SPR) and isothermal titration calorimetry (ITC) were used to validate our new FRET method, and the accuracy of our FRET assay was shown to be similar to the established techniques. With its advantages over SPR and ITC owing to its high sensitivity, small sample size, straightforward technique and the possibility for high-throughput expansion, we envision that our solution-based method can be applied in pre-miRNA–target binding studies.